MANAJEMEN ORGANISASI SANGGAR SENI BORNEO TARIGAS DI KOTA PONTIANAK - Gew, Dorotea Rebika; Ismunandar, Ismunandar; Aditya, Mega Cantik Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study explores the organizational management of Borneo Tarigas Art Studio in Pontianak City, which has consistently developed its artistic achievements and maintained cultural preservation. The research aims to describe the management functions and elements implemented, including planning, organizing, actuating, controlling, financial management, methods, materials, facilities, learning content, and marketing strategies. This research employed a qualitative descriptive method with a sociological approach. Data were collected through interviews, observations, and documentation, with the validity of data ensured through source triangulation and extended observation. Findings indicate that the studio applies systematic and effective management practices, enabling it to sustain its artistic programs, foster talent development, and maintain organizational resilience amidst challenges such as the COVID-19 pandemic. The study concludes that effective organizational management is crucial for cultural art studios to remain sustainable and competitive.